The Effect of Zinc, Copper, and Silver Ions on Oat (Avena sativa L.) Androgenesis - Marzena Warchoł; Katarzyna Juzoń; Kinga Dziurka; Ilona Czyczyło-Mysza; Kamila Kapłoniak; Izabela Marcińska; Edyta Skrzypek (Plants, 2021)
Oat (Avena sativa L.) cultivars ‘Bingo’ and ‘Chwat’ were used to compare the embryogenesis competence of another culture. Despite the embryo-like structures obtained from both tested cultivars, only ‘Chwat’ produced green plantlets, which confirmed the cultivar dependency. ‘Chwat’ produced the highest number of embryo-like structures and green plantlets (0.7/100 anthers and 0.1/100 anthers, respectively). The embryo-like structure formation also depended on cold pretreatment combined with Cu2+, Zn2+, or Ag+ ion supplementation, which was applied during the tiller pretreatment or added to the induction media. The highest number of embryo-like structures (2.1/100 anthers) were observed on anthers derived from the tillers kept in a 50% Hoagland medium with the addition of 10 µM of CuSO4. In turn, the induction media supplemented with the ions Cu2+, Zn2+, or Ag+ increased neither the number of embryo-like structures nor the green plantlet production compared to the control conditions. However, such ion applications turned out to be most effective when the induction medium was enriched with 25 µM of AgNO3 and left to obtain the highest number of embryo-like structures and green plantlets (0.8/100 anthers and 0.2/100 anthers, respectively). Therefore, more attention should be paid to the possibilities of adjusting the media nutrient composition, as this may be the only way to significantly increase the efficiency of this method.